TECHNO-ECONOMIC ANALYSIS FOR THE PRODUCTION OF BUTYL CELLOSOLVE ACETATE AND EO-3 PHOSPHATE ESTER - KULDIP SINGH, LUPETE KAUR BHULLAR (IRC, 2017)
The author’s SIP research concludes that among the grades of BGE Esters and Phosphate Esters, Butyl Cellosolve Acetate (BCA) and EO-3 Phosphate Ester are the most feasible to manufacture. This is because only mild operating conditions is required. These esters also offer large variety of applications. This study is continued to support PETRONAS’ strategy to expand the markets of their ether products. This in return aids in achieving profit in the company. This report thus analyses on the economic feasibility of BCA and EO-3 Phosphate Ester. The esterification reactions involved are between Butyl Cellosolve and Acetic Acid and between Tergitol 26L-3 and Phosphoric Acid. The products are BCA and EO-3 Phosphate Ester respectively. The yield of BCA and EO-3 Phosphate Ester is calculated to be and 64.79% and 50% respectively. The process was developed and simulated in Aspen HYSYS V8.8. BCA process shows the formation of three azeotropic mixtures which causes separation to be difficult. On the other hand, EO-3 Phosphate Ester shows the formation of aqueous phosphoric acid that is difficult to separate. Fortunately, there is market for this aqueous mixture. Hence, it is sold. Monte Carlo simulation are done for parameter uncertainties such as the CAPEX estimate, raw material price and product prices. This simulation shows that the economic potential of EO-3 Phosphate Ester is at least 200 % higher than that of BCA. Based on the results obtained, it can be concluded that EO-3 phosphate ester is the most profitable ester to produce.